National Health Examination Survey, Cycle I, 1959-1962: Osteoarthritis and Rheumatoid Arthritis Data ([Verlag nicht ermittelbar], 1989)
The National Health Examination Surveys, Cycle I (NHES I), conducted during the period 1959-1962, were designed to secure statistics on the health status of the population of the United States. More specifically, their purpose was to determine the prevalence of certain chronic diseases, the status of dental health, and the distributions of auditory and visual acuity and certain anthropometric measurements. Included in this collection are findings pertaining to osteoarthritis and rheumatoid arthritis from x-rays of the hands and feet, medical history items, and a physician's examination.